A case study of improved PEO assessments in the electrical, electronic and systems engineering program at Universiti Kebangsaan Malaysia - Nor Fadzilah Abdullah,; Fazida Hanim Hashim,; Siti Salasiah Mokri,; Nasharuddin Zainal,; Mohd Hafiz Baharudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Program educational objectives (PEOs) encompass a collection of statements that outline the knowledge, proficiencies, and competencies that graduates of a program should possess. PEO assessments are conducted for the purpose of evaluating the degree to which students have attained these objectives. However, the current assessment methods are not comprehensive and do not provide sufficient data to determine whether graduates are achieving the intended outcomes of the program. As a result, the program may not have sufficient data to provide informed decisions about curriculum development and student support services. This study provides an examination of the recently implemented Program Educational Objectives (PEO) evaluations within the undergraduate program of Electrical, Electronic and Systems Engineering, at the Faculty of Engineering and Built Environment, Universiti Kebangsaan Malaysia (UKM). This study examines the difficulties encountered during the development and execution of direct and indirect PEO evaluations, along with the measures undertaken to enhance these assessments. It also includes a quantitative analysis of the findings generated from the newly implemented PEO assessment questionnaires. The study concludes by providing a discussion of the advantages associated with enhancing PEO assessments, as well as the potential usage for other engineering programs within the faculty.